2010
DOI: 10.1111/j.1743-6109.2009.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

History of Sexual and Physical Abuse in Women with Dyspareunia: Association with Pain, Psychosocial Adjustment, and Sexual Functioning

Abstract: Aim Dyspareunia is a women’s sexual health problem that still often goes undiagnosed despite its high prevalence and its detrimental impact on sexual, relationship, and psychological adjustment. Although sexual and physical abuse may constitute risk factors for the development of dyspareunia, the effects of past abuse on current pain and associated sexual and psychosocial impairments have never been examined. Thus, the aim of this study is to determine the relation between a history of sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 45 publications
(89 reference statements)
1
28
1
2
Order By: Relevance
“…An important factor that has been repeatedly linked to both sexual functioning and sexual distress, and which may serve a similar moderating role, is a history of childhood sexual abuse (CSA), defined here as unwanted sexual contact before the age of 16. Many studies have found that women with a history of CSA report poorer sexual functioning than women without a history of sexual abuse (NSA) across the lifespan (Dennerstein, Guthrie, & Alford, 2004), and have a higher prevalence of sexual dysfunction (Kinzl, Traweger, & Biebl, 1995; Leclerc, Bergeron, Binik, & Khalife, 2010; Loeb et al, 2003; Najman, Dunne, Purdie, Boyle, & Coxeter, 2005; Sarwer & Durlak, 1996). Women with CSA histories also report lower levels of sexual satisfaction relative to NSA women (Browne & Finkelhor, 1986; Jackson, Calhoun, Amick, Maddever, & Habif, 1990), as well as greater levels of sexual distress (Merrill et al, 2003; Rellini & Meston, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An important factor that has been repeatedly linked to both sexual functioning and sexual distress, and which may serve a similar moderating role, is a history of childhood sexual abuse (CSA), defined here as unwanted sexual contact before the age of 16. Many studies have found that women with a history of CSA report poorer sexual functioning than women without a history of sexual abuse (NSA) across the lifespan (Dennerstein, Guthrie, & Alford, 2004), and have a higher prevalence of sexual dysfunction (Kinzl, Traweger, & Biebl, 1995; Leclerc, Bergeron, Binik, & Khalife, 2010; Loeb et al, 2003; Najman, Dunne, Purdie, Boyle, & Coxeter, 2005; Sarwer & Durlak, 1996). Women with CSA histories also report lower levels of sexual satisfaction relative to NSA women (Browne & Finkelhor, 1986; Jackson, Calhoun, Amick, Maddever, & Habif, 1990), as well as greater levels of sexual distress (Merrill et al, 2003; Rellini & Meston, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Controlled research has supported an association between these factors in women with chronic pelvic pain [67] and vaginismus [52]; however, findings have been inconsistent in women with vulvodynia [68][69][70]. A recent study found that psychological and sexual function were lower in women with dyspareunia who had experienced penetrative sexual abuse [71]. Therefore, although sexual abuse may not be more common in women with sexual pain disorders than in the general population, experiencing such abuse may be related to more severe psychological and sexual sequelae.…”
Section: Sexual Abusementioning
confidence: 98%
“…Is the use of self-administered questionnaires really helpful in the evaluation at pretreatment of neurotic patients with accompanying sexual dysfunction? Other investigators, particularly in Polish studies [40], have reported predominantly on data from questionnaires devoted to certain sexual dysfunctions [20][21] and to specific subpopulations [17][18]36].…”
Section: Discussionmentioning
confidence: 99%
“…They affect orgasm and/or sexual drive, disturb relationships [18], and predict vestibulodynia [19], dyspareunia [20], and vulvodynia [21]. For instance, the latter is estimated 4.4 times more likely to be reported if the perpetrator was a primary family member, and 6.5 times if the abuse was frequent.…”
Section: Introductionmentioning
confidence: 99%